168 Evaluation of Increasing Dietary Threonine to Lysine Ratio in Corn-Soybean Meal Diets with and Without Dried Distillers Grains with Solubles (DDGS) on Growth Performance of Grow-Finish Pigs. (12th April 2022) - Tolosa Russi, Andres F; Tokach, Mike D; Goodband, Robert D; Gebhardt, Jordan T; Woodworth, Jason C; DeRouchey, Joel M
Abstract: A total of 2, 160 pigs (PIC 337×1050; initial BW 35.1 kg) were used in a 112-d growth trial to evaluate the effects of normal or high SID Thr:Lys ratio in diets with and without DDGS on growth performance. Pigs were assigned to pens (27 pigs per pen) in a randomized complete block design by BW with 20 replications per treatment. Pens of pigs were allotted to 1 of 4 dietary treatments arranged in a 2×2 factorial with main effects of dietary Thr level (Normal vs High) and DDGS (with or without). Treatment diets were formulated in 4 phases from 35 to 57, 57 to 82, 82 to 105, and 105 to 136 kg BW. Diets with high DDGS were formulated to include 40% DDGS in phase 1 and 2, 30% in phase 3, and 15% in phase 4. Normal Thr diets were formulated to contain 61, 62, 63, and 65% SID Thr:Lys ratios for the 4 dietary phases, respectively. High Thr diets had SID Thr:Lys ratios of 67, 68, 69 and 72%, respectively. There were no (P>0.10) DDGS×Thr interactions. For the overall period (d 0 to 112), pigs fed diets without DDGS had increased ( P < 0.001) ADG and BW, and reduced ( P < 0.001) ADFI leading to improved ( P < 0.001) G:F. There was no evidence for difference ( P > 0.10) between diets with normal or high SID Thr:Lys ratio regardless of DDGS inclusion. In summary, the addition of high levels of DDGS reduced ADG and increased ADFI, which resulted in poorer G:F and lighter final BW, regardless of the dietary SID Thr:Lys ratio. These results indicate that addition of an insoluble fiber source, such as corn DDGS, does not increase the Thr:Lys requirement of finishing pigs.